FINANCING OF DIGITAL TECHNOLOGIES FOR EDUCATION AT SECONDARY SCHOOLS - SIMBARTL, Petr (Trends in education, 2015)
The article discusses the financing of digital technologies for pupils at secondary school. Using the questionnaire (method Paper And Pen Interviewing) we find parents' opinions on financing. We evaluated data from 76 respondents. The results compare with financing another project. We looking information, how the financing of digital technology abroad.
Keywords: digital technology; tablet; Education.